The politics of locating the third spinning mill in Southern Rhodesia, 1951-1953 (Historia, 2021)
The textile industry in Southern Rhodesia witnessed rapid growth during and after the Second World War. The industry was largely dependent on locally grown cotton and the capacity to spin the cotton into yarn. The cotton Industry and Research Board (CRIB) established to oversee the development of the cotton industry in the colony, constructed the first spinning mill in Gatooma in 1943 with a capacity of 1 000 spindles, which was later increased to 35 000 spindles with the construction of the No. 2 mill in 1951. In the same year the government sanctioned the construction of a third mill, but it was not immediately built. The increase in the number of industrial concerns using the CRIB yarn and the expected expansion of textile demands from a wider federal market from 1953, generated debate in government, business circles and by interested parties on the possible location of the third mill. This article examines these debates that have largely escaped the attention of scholars who have largely focused on other aspects of the textile industry. For reasons that are not very clear, friction between the CRIB and the municipality of Gatooma developed to the extent that the Board expressed the desire to locate the additional mill (and thereby increase the spinning capacity of the industry) in other parts of the country rather than in Gatooma. The municipality was supported by interest groups that were motivated by the desire to retain the spinning industry in Gatooma. The article is not just about the third mill; it also examines how this struggle informs us about other aspects of the political economy of colonial Zimbabwe. Die tekstielnywerheid in Suid-Rhodesië het getuig van snelle groei tydens en na die Tweede Wêreldoorlog. Die nywerheid was hoogs afhanklik van plaaslik verboude katoen en die kapasiteit om die katoen in draad te spin. Die katoennywerheid en Navorsingsraad (Cotton Research and Industry Board - CRIB), wat tot stand gebring is om toesig te hou oor die ontwikkeling van die katoennywerheid in die kolonie, het in 1943 die eerste spin-meule, met 'n kapasiteit van 1 000 spin-spille, opgerig, wat later tot 35 000 spin-spille uitgebrei is met die oprig van meule Nr 2 in 1951. In dieselfde jaar het die regering 'n derde meule goedgekeur, maar dit is nie onmiddellik gebou nie. Die toename in die aantal nywerheidsake wat die CRIB-draad gebruik het en die verwagte toename in tekstielaanvraag uit 'n breër federale mark sedert 1953 het debat in die regering en onder sakegroepe en belanghebbende partye ontlok oor die moontlike ligging van die derde meule. Hierdie artikel gaan in op hierdie debatte wat die aandag van vakkundiges, wat hoofsaaklik op ander aspekte van die tekstielnywerheid gefokus het, grootliks ontglip het. Weens redes wat nie baie duidelik is nie, het wrywing tussen die CRIB en die munisipaliteit van Gatooma ontwikkel - in dié mate dat die Raad die begeerte uitgespreek het om die bykomstige meule (en daardeur die weefkapasiteit van die nywerheid) in ander dele van die land, eerder as in Gatooma, te vestig. Die munisipaliteit is ondersteun deur belangegroepe wat deur die begeerte gemotiveer is om die spinnywerheid in Gatooma te behou. Die artikel handel nie alleen oor die derde meule nie; dit ondersoek ook hoe hierdie stryd ons inlig oor ander aspekte van die politieke ekonomie van koloniale Zimbabwe.